2019
DOI: 10.1093/ecco-jcc/jjz044
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Transition Outcomes in Inflammatory Bowel Disease: A Multinational Delphi Study

Abstract: Background Transition programmes are designed to prepare adolescent inflammatory bowel disease [IBD] patients for transfer to adult care. It is still unclear which outcome parameters define ‘successful transition’. Therefore, this study aimed to identify outcomes important for success of transition in IBD. Methods A multinational Delphi study in patients, IBD nurses, and paediatric and adult gastroenterologists was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Ulcerative colitis (UC) is a complex, chronic and non-specific inflammatory condition of the gastrointestinal tract ( 1 ). It is one of the most common subtypes of inflammatory bowel disease ( 2 ). The etiology of UC remains unclear, although it is considered to involve genetic, environmental and immunological factors, all of which contribute to the disease at least in part by interacting with the gut microbiota ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a complex, chronic and non-specific inflammatory condition of the gastrointestinal tract ( 1 ). It is one of the most common subtypes of inflammatory bowel disease ( 2 ). The etiology of UC remains unclear, although it is considered to involve genetic, environmental and immunological factors, all of which contribute to the disease at least in part by interacting with the gut microbiota ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the most up-to date observations, individual, healthcare service and social outcomes should be taken equally into account as composite endpoints of a transition process in IBD. [4][5][6] Transitional interventions In a recent systematic review, several different structured transition interventions were identified aiming to improve transition-related outcomes. 7 Joint visits were the most frequently applied interventions, which were held under different circumstances and were organised by multidisciplinary groups of different compositions all around the world.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Based on the recommendation of a recently conducted multinational Delphi study on the transition care of adolescent with IBD, HRQoL should be assessed with IMPACT-III questionnaire at 1-year post-transfer. 6…”
Section: Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…An international Delphi study conducted by experts of transitional care from 15 countries, including physicians, nurses, psychologists, transition program managers, and research director, presented key elements for, and indicators of, a successful transition [32]. Similarly, a multinational expert panel made up of IBD nurses and pediatric and adult gastroenterologists investigated the outcomes that reflect successful transition in IBD patients using a Delphi method [33]. The principal key elements are shown in Table 2.…”
Section: Key Elements For a Successful Transitionmentioning
confidence: 99%